2017
DOI: 10.3389/fphys.2017.00822
|View full text |Cite
|
Sign up to set email alerts
|

Alternation of Gut Microbiota in Patients with Pulmonary Tuberculosis

Abstract: One-third of the world's population has been infected with Mycobacterium tuberculosis (M. tuberculosis), a primary pathogen of the mammalian respiratory system, while about 10% of latent infections progress to active tuberculosis (TB), indicating that host and environmental factors may determine the outcomes such as infection clearance/persistence and treatment prognosis. The gut microbiota is essential for development of host immunity, defense, nutrition and metabolic homeostasis. Thus, the pattern of gut mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(154 citation statements)
references
References 25 publications
7
128
2
2
Order By: Relevance
“…These studies revealed that bacterial diversity in the gut of TB patients is altered and this may correlate with the progress of the disease (Luo et al, 2017;Maji et al, 2018). These studies revealed that bacterial diversity in the gut of TB patients is altered and this may correlate with the progress of the disease (Luo et al, 2017;Maji et al, 2018).…”
Section: Tuberculosismentioning
confidence: 90%
See 1 more Smart Citation
“…These studies revealed that bacterial diversity in the gut of TB patients is altered and this may correlate with the progress of the disease (Luo et al, 2017;Maji et al, 2018). These studies revealed that bacterial diversity in the gut of TB patients is altered and this may correlate with the progress of the disease (Luo et al, 2017;Maji et al, 2018).…”
Section: Tuberculosismentioning
confidence: 90%
“…Gut microbiota has been analysed during the course of TB infections and also during anti-TB treatment in humans. These studies revealed that bacterial diversity in the gut of TB patients is altered and this may correlate with the progress of the disease (Luo et al, 2017;Maji et al, 2018). Anti-TB therapy includes antibiotics, such as rifampicin, that target bacteria other than mycobacteria, and one study showed that prolonged anti-TB treatment broadly alters the gut microbiota of TB patients and that the resulting dysbiotic state persists following cessation of therapy (Wipperman et al, 2017).…”
Section: Chronic Bacterial Infections: the Case Ofmentioning
confidence: 99%
“…The findings above, nevertheless, differed from three studies conducted in China (Table 1). 6,14,30 In particular, the studies in China observed changes in species diversity and abundance between healthy and TB patients. Unfortunately, the antimicrobials used by the cohorts in China, except for one study that used HRZE, 30 were not delineated, as was the case in Haiti (Table 1).…”
Section: Antimicrobials: the Major Enemy Of The Microbiomementioning
confidence: 99%
“…(Table 1). 6,14 Nevertheless, HRZE exposure reduced genera belonging to Clostridiales, such as Ruminococcus spp., Ruminococcus gnavus, and Faecalibacterium spp., while Bacteroidetes members, such as Bacteroides spp. (B. fragilis, B. plebeius, B. caccae, and B. coprophilus), and Parabacteroides distasonis, were significantly enriched.…”
Section: Antimicrobials: the Major Enemy Of The Microbiomementioning
confidence: 99%
See 1 more Smart Citation